Theism and Realism: A Match Made in Heaven? - Hewitt, Simon Thomas (European journal for philosophy of religion, 2018)
There is no interesting entailment either way between theism and various forms of realism. Taking its cue from Dummett's characterisation of realism and his discussion of it with respect to theistic belief, this paper argues both that theism does not follow from realism, and that God cannot be appealed to in order to secure bivalence for an otherwise indeterminate subject matter. In both cases, significant appeal is made to the position that God is not a language user, which in turn is motivated by an account of understanding as aptitude possession. The resulting picture sits comfortably with the apophatism common within living religious traditions and with the view that the philosophy of religion ought to reorientate itself away from metaphysics towards more practical questions.